Statistical analysis of surface roughness of machined graphite by means of CNC milling (2016)
The aim of this research is to analyze the influence of cutting speed, feed rate and cutting depth on the surface finish of grade GSP-70 graphite specimens for use in electrical discharge machining (EDM) for material removal by means of Computer Numerical Control (CNC) milling with low-speed machining (LSM). A two-level factorial design for each of the three established factors was used for the statistical analysis. The analysis of variance (ANOVA) indicates that cutting speed and feed rate are the two most significant factors with regard to the roughness obtained with grade GSP-70 graphite by means of CNC milling. A second order regression analysis was also conducted to estimate the roughness average (Ra) in terms of the cutting speed, feed rate and cutting depth. Finally, the comparison between predicted roughness by means of a second order regression model and the roughness obtained by machined specimens considering the combinations of low and high levels of roughness is also presented.